Faktor Domestik Penolakan Italia terhadap Pengungsi dari Afrika Utara tahun 2015-2019 - Harlianto Wicaksono, Louis; Fauzan Alamari, Muhammad (Jurnal Ilmiah Hubungan Internasional Fajar, 2022)
The wave of refugees that was initiated by the Arab Spring phenomenon has increased the number of refugee arrivals in Italy starting in 2015. Refugees from North Africa who use the Central Mediterranean Route to reach mainland Italy pose a new threat to the Italian government related to the refugee crisis that occurred. The anti-refugee stance formed by the Italian government which was implemented through the Closed Port Policy and the Salvini Decree-Law on Immigration is a policy that was formed after the victory of the right-wing party in Italy. Italy's repressive policies, which exclude international law from the 1951 Convention and the European Union's CEAS on the issue of refugees, become an interesting topic to study how the domestic. level has a major influence on the rejection of refugees by the Italian government. In explaining how the role of the domestic level influences foreign policy, the author uses the concept of Neoclassical Realism by Gideon Rose which is supported through a qualitative method approach with data collection techniques in the form of literature studies. Based on the discussion and analysis, there are three points on how the domestic level plays a major role in the policy of rejecting refugees from North Africa. First, the use of the Put Italian First identity as a nationalist spirit generator by Salvini. Second, there is pressure from interest groups and parties to adopt their interests. Third, the anti-refugee factor of Salvini's leadership made the government exclude international law on refugees.